2019
DOI: 10.3390/polym11040713
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Direct Synthesis of HKUST-1 in Wool Fabric for the Improvement of Antibacterial Properties

Abstract: The use of Metal-Organic Frameworks (MOF) such as HKUST-1 in textiles is an alternative with regard to the development of technologies that are increasingly seeking for functionalities, mainly in the fields of health and hygiene, named biofunctional fabrics. However, the application of the MOF under the surface of the wool fiber can lead to a low durability finish due to its low fixation. Thus, this project aims to perform the direct synthesis of HKUST in the wool fiber, so that a product with good washing dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…Three diffraction peaks at 2θ of 16°, 22.5° and 35° could be attributed to the (101), ( 002) and ( 040) crystal faces of cellulose, respectively. And the new peaks at 6.6°, 9.5° and 11.5° corresponding to the (200), ( 220) and ( 222) crystal faces of MOF199, which are well consist with other literature (Lis et al 2019;Loera-Serna et al 2012;Wang et al 2015). The XRD analysis indicated that the successful synthesis of MOF199 on bamboo.…”
Section: Antibacterial Testsupporting
confidence: 74%
See 1 more Smart Citation
“…Three diffraction peaks at 2θ of 16°, 22.5° and 35° could be attributed to the (101), ( 002) and ( 040) crystal faces of cellulose, respectively. And the new peaks at 6.6°, 9.5° and 11.5° corresponding to the (200), ( 220) and ( 222) crystal faces of MOF199, which are well consist with other literature (Lis et al 2019;Loera-Serna et al 2012;Wang et al 2015). The XRD analysis indicated that the successful synthesis of MOF199 on bamboo.…”
Section: Antibacterial Testsupporting
confidence: 74%
“…According to previous reports, MOF have been successfully synthesized onto different bio-based materials, such as cellulose ber (Ma et al 2018;Wang et al 2015), wool fabric (Lis et al 2019), cotton fabric (Abdelhameed et al 2016;Emam et al 2016), which all have loose and porous structures and facilitate the attachment of MOF (Duan et al 2018). In cellulose materials, various efforts have been made to improve the attachment between MOF and the substrate by introducing carboxyl groups, such as carboxymethylation (Duan et al 2019a), TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl radical)-mediated oxidation (Duan et al 2019b), hydrogen peroxide oxidation (Abdelhameed et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In all spectra, the peaks at 1271 cm −1 for the C–H group in the SiCH 3 group and 778 cm −1 for the Si–C group demonstrated that the methyl group was connected to the Si atom directly [31]. The peak at 2561 cm −1 for the SH group were observed in POMs, which proved the successful formation of mercaptopropyl-functionalized POMs [32]. The same peak at 2561 cm −1 for the SH group became weaker after loading Au nanoparticles due to the interaction between thiols and gold surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative method, a test was used to evaluate the antibacterial activity of both ZnO and CuO nanofibers according to ASTM E 2149-01 (standard test method for determining the antibacterial activity of immobilized antimicrobial agents under dynamic contact conditions) [ 24 ]. The antibacterial functions of the electrospun nanofibrous membranes were expressed as the percentage reduction of test organisms after a specified contact time with the nanofibers and according to the following formula: …”
Section: Methodsmentioning
confidence: 99%